OBOR CHINA, AS DAN RESPON ULAMA INDONESIA - Herdi Sahrasad (Jisiera: The Journal of Islamic Studies and International Relations, 2019)
The success of China’s economic modernization surprised the international community. The 21st Century is the Asian Century that is hegemonized  by China where there  is no  guarantee that China will consistently uphold “peaceful cooperation and coexistence” with neighboring countries in Southeast Asia. In 2050, half of the world’s gross national product will be controlled by Asia which China is predicted to displace the US to second place and become the world’s strongest player, followed by India in third place. Today, the world is witnessing: China which is authoritarian and rejects liberal democracy, continues to grow its military and economic power. The impact of China’s military and economic growth is increasingly felt by developing countries in Southeast Asia. “The threat of China,” a term that is often echoed by the US/West lately, is because China not only militarily great, but rather economically. Multaqo Ulama Ahlussunnah Waljamaah which was attended by thousands of Ulama, Habaib, Kyai, Caretakers of Islamic Boarding Schools throughout Indonesia who gathered at the Darussalam Boarding School in Wanaraja Garut, West Java on May 12, 2019 had expressed rejection of the People's Republic of China One Belt One Road program.